2007
DOI: 10.1159/000110638
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-9 Is Involved in the Development and Plasticity of Retinotectal Projections in Rats

Abstract: Objective: During postnatal development, retinotectal projections undergo a process of misplaced axon elimination, leading to a topographical matching between the retinal surface and the superior colliculus. Matrix metalloproteinases (MMPs) have been implicated in the development and plasticity of the nervous system. We studied the expression and role of MMPs during normal development of retinotectal projections and after monocular enucleation-induced plasticity. Material and Methods: Lister hooded rats at dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 57 publications
1
31
1
Order By: Relevance
“…MMP-9 function has been implicated in synaptic plasticity and long-term potentiation by extracellular proteolysis [3336]. However, our data failed to hint at a direct involvement of MMP-9 in synaptogenesis following deafferentation of AVCN due to cochlear ablation.…”
Section: Discussioncontrasting
confidence: 83%
“…MMP-9 function has been implicated in synaptic plasticity and long-term potentiation by extracellular proteolysis [3336]. However, our data failed to hint at a direct involvement of MMP-9 in synaptogenesis following deafferentation of AVCN due to cochlear ablation.…”
Section: Discussioncontrasting
confidence: 83%
“…In rats, the critical period of these pathways extend until the third postnatal week [20]. Previously, our group demonstrated that different mechanisms are involved in the retinotectal development and plasticity [21,22,23,24]. Recently, we have shown that IL-2 intravitreous treatment during the critical period results in a sprouting of uncrossed retinotectal axons [25] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it seems that inflammation modulates extracellular proteolytic activity that in turn regulates plasticity. Indeed, it has been shown that axonal sprouting in response to a lesion in the visual system depends on the activity of MMP-9 [54]. …”
Section: Inflammation and Lesion-induced Plasticity In The Cnsmentioning
confidence: 99%